2021
DOI: 10.5705/ss.202018.0334
|View full text |Cite
|
Sign up to set email alerts
|

Doubly Robust Regression Analysis for Data Fusion

Abstract: This paper investigates the problem of making inference about a parametric model for the regression of an outcome variable Y on covariates (V, L) when data are fused from two separate sources, one which contains information only on (V, Y ) while the other contains information only on covariates. This data fusion setting may be viewed as an extreme form of missing data in which the probability of observing complete data (V, L, Y ) on any given subject is zero. We have developed a large class of semiparametric e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Unfortunately, the CEX provides limited information on wealth data and thus the CEX alone is not sufficient for our purposes. Previous research (Bostic et al, 2009) (Bostic et al, 2009), we truncate the SCF sample at 90th percentiles of observed total household income and net worth, as was done in Evans et al (2021).…”
Section: Applicationmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, the CEX provides limited information on wealth data and thus the CEX alone is not sufficient for our purposes. Previous research (Bostic et al, 2009) (Bostic et al, 2009), we truncate the SCF sample at 90th percentiles of observed total household income and net worth, as was done in Evans et al (2021).…”
Section: Applicationmentioning
confidence: 99%
“…Because there are missing values in the original survey data, the publicly available data set consists of five imputed replicates. We thus follow Evans et al (2021) to perform estimation for each replicate and combine the results using Rubin's rule (Rubin, 2004). We report the point estimates and standard errors of our analysis results using all the four working models in Table 2.…”
Section: Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider a regression model for the outcome on all available covariates measured in the internal study, while using information from multiple external data sources, which Evans et al (2018) refer to as the regression analysis for data fusion.…”
Section: Introductionmentioning
confidence: 99%